AN ASSESSMENT OF STUDENTS’ NEEDS AND EXPECTATIONS REGARDING GUIDANCE SERVICES IN PHRAPARIYATTIDHAMMA SCHOOL, GROUP 13 - Changkulg, PhraSarun; Woramongkhalo, PhrakhrupaladMarut; Mererk, Sayyud (Journal of Educational Review Faculty of Education in MCU, 2026)
The objectives of this research article were: 1) to study the needs and expectations regarding guidance services of students at Phrapariyattidhamma School in Group 13; 2) to compare the needs and expectations regarding guidance services of students at Phrapariyattidhamma School in Group 13, classified by students’ personal factors; and 3) to study the factors related to the needs and expectations regarding guidance services of students at Phrapariyattidhamma School in Group 13. This research was a mixed-methods study, using questionnaires to collect quantitative dada from a sample of 155 students from Phrapariyattidhamma School in Group 13, and an interview to collect qualitative data from 6 key informants including the director and guidance counselors of the school. Data analysis included means, standard deviations, t-tests, One-way ANOVA, Pearson correlation analysis, and content analysis. Findings of the study were as follows: 1) The overall need for guidance services of students at Phrapariyattidhamma School in Group 13 was at the highest level across all dimensions, with the individual student data collection service having the highest average, followed by the service for tracking results, counseling services, information services, and personal placement services, respectively. Regarding students’ expectations, the overall level was high across all aspects, with the personal placement service having the highest average, followed by the information service, guidance services, individual student data collection services, and result tracking services, respectively. 2) Students with different ages, grade levels, and religious education levels showed significant statistical differences in their overall needs and expectations for guidance services at the 0.05 level. In contrast, variations in the length of ordination (years in the monkhood) did not result in significant differences in their needs or expectations. 3) Self-confidence, motivation, attitude towards self-development, and the quality of services all showed a positive correlation with the needs and expectations for guidance services of students at Phrapariyattidhamma School in Group 13, with statistical significance at the 0.05 level.